Morphotypes and genetic diversity of Dendrobaena schmidti (Lumbricidae, Annelida) - S. V. Shekhovtsov; I. B. Rapoport; T. V. Poluboyarova; A. P. Geraskina; E. V. Golovanova; S. E. Peltek (Вавиловский журнал генетики и селекции)
Dendrobaena schmidti (Michaelsen, 1907) is a polymorphic earthworm species from the Caucasus and adjacent regions. Adult D. schmidti individuals have highly variable body size (from 1.5 to well over 10 cm) and color (from dark purple to total lack of pigmentation), so a lot of subspecies of D. schmidti have been described; however, the existence of most of them is currently under dispute. We studied the genetic diversity of D. schmidti from seven locations from the Western Caucasus using mitochondrial (a fragment of the cytochrome oxidase I gene) and nuclear (internal ribosomal transcribed spacer 2) DNA. For both genes studied, we found that our sample was split into two groups. The first group included somewhat bigger (3-7.5 cm) individuals that were only slightly pigmented or totally unpigmented (when fixed by ethanol). The second group contained small (1.7-3.5 cm) specimens with dark purple pigmentation. In one of the studied locations these two groups were found in sympatry. However, there were no absolute differences either in general appearance (pigmented/unpigmented, small/big) or among diagnostic characters. Although the two groups differed in size (the majority of individuals from the first group were 5-6 cm long, and of the second one, 2-3 cm), the studied samples overlapped to a certain degree. Pigmentation, despite apparent differences, was also unreliable, since it was heavily affected by fixation of the specimens. Thus, based on the obtained data we can conclude that D. schmidti consists of at least two species that have identical states of diagnostic characters, but differ in general appearance.